Dinamika Pemanfaatan Lahan Pesisir Kabupaten Indramayu dengan Pendekatan DPSIR (Driver, Pressures, States, Impact dan Responses) - Sodikin Sodikin; Mujio Mujio; Santun R.P Sitorus; Siti Umamah Naili Muna (Jurnal Zona, 2023)
The purpose of this research is to examine coastal dynamics in Indramayu District using the DPSIR method, which is hypothesized to help researchers understand the influence of human actions on land and sea on coastal ecosystems. A descriptive research strategy based on the Driver, Pressures, States, Impact, and Responses (DPSIR) framework was used. Primary data collected through in-depth interviews and observations became the backbone of this research, while secondary data came from affiliated institutions and organizations.Analysis shows that rapid population growth in the Indramayu region has led to a significant increase in land use along the coast. Conversion of mangrove forests into other uses, such as pond cultivation, agriculture, tourist attractions, and settlements, is common when associated with land conversion. Coastal and mangrove ecosystems, air quality and biodiversity are just a few examples of the physical, chemical and biological changes that result from these changes. Apart from reducing fishery yields, impacts such as abrasion and mangrove deforestation reduce the carrying capacity of land and reduce environmental quality. Efforts to increase community participation in island management are carried out to overcome this, including the construction of breakwaters, mangrove rehabilitation, socialization of the community regarding sustainable fisheries, as well as increasing the value of fishery products and mangrove ecosystem services. Minimize environmental impact and stay small